2003
DOI: 10.1021/jp0354200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluorination on Self-Assembled Monolayer Formation from Alkanephosphonic Acids on Aluminum:  Kinetics and Structure

Abstract: We have used infrared spectroscopy, ellipsometry, and contact angle measurements to study self-assembled monolayer (SAM) formation on aluminum native oxide from three alkanephosphonic acids:  CF3(CF2)7(CH2)11PO3H2 (F8H11PA), and CH3(CH2) n PO3H2 (n = 15 (H16PA); n = 21 (H22PA)). These compounds show significant differences in film structure and film formation kinetics. Strikingly, the methylene segment of the semifluorinated F8H11PA SAM never reaches an ordered state even at long assembly times. This contrasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
130
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(152 citation statements)
references
References 70 publications
(150 reference statements)
21
130
1
Order By: Relevance
“…Different studies with octadecylphosphonic acid (OPDA) [176][177][178] on metal oxide supports showed the formation of well-ordered monolayers with high grafting densities of about 4 groups/nm -2 . Self-assembly monolayers, comprising the molecules of three phosphonic acids, namely CF 3 (CF 2 ) 7 (CH 2 ) 11 PO 3 H 2 , n-C 16 H 33 PO 3 H 2 and n-C 22 H 45 PO 3 H 2 , on the surface of aluminium metal covered with a native oxide film were studied [179]. These authors demonstrated that in all cases a monolayer is formed, however, in the case of the fluorinate acids more time is needed.…”
Section: Phosphorous Coupling Agents As Surface Modifiersmentioning
confidence: 99%
“…Different studies with octadecylphosphonic acid (OPDA) [176][177][178] on metal oxide supports showed the formation of well-ordered monolayers with high grafting densities of about 4 groups/nm -2 . Self-assembly monolayers, comprising the molecules of three phosphonic acids, namely CF 3 (CF 2 ) 7 (CH 2 ) 11 PO 3 H 2 , n-C 16 H 33 PO 3 H 2 and n-C 22 H 45 PO 3 H 2 , on the surface of aluminium metal covered with a native oxide film were studied [179]. These authors demonstrated that in all cases a monolayer is formed, however, in the case of the fluorinate acids more time is needed.…”
Section: Phosphorous Coupling Agents As Surface Modifiersmentioning
confidence: 99%
“…An important role in the interest to SAMs on Al and its alloys belongs to the results obtained in [42]. Its authors used IRS, ellipsometry, and measurements of the  angle to study SAM on natural Al oxide formed by three APhs: CF 3 (CF 2 ) 7 (CH 2 ) 11 PO 3 H 2 (APhC 19 F 17 ); APhC 16 and APhC 22 .…”
Section: Mono-and Diphosphonic Acids and Their Saltsmentioning
confidence: 99%
“…Assembly of organic species on conducting substrates in the form of molecular wires and molecular assemblies have been widely studied, and within recent years, research have increased in polymer assemblies on varies conducting substrate [3,4,12]. Conjugated polymers end-functionalized with phosphonic acid anchoring groups have been grafted onto oxide substrates such as indium tin oxide (ITO) [5,[13][14][15][16], zinc oxide [17], silicon dioxide (SiO 2 ) [18], titanium dioxide (TiO 2 ) [19,20], and aluminium oxide (Al 2 O 3 ) [21]. Through a dehydration (condensation) reaction, the phosphonic acid group binds to each substrate covalently and possibly electrostatically (via hydrogen bonds), producing several binding modes [15].…”
Section: Archivos De Medicina Issn 1698-9465mentioning
confidence: 99%